PENYELESAIAN KREDIT BERMASALAH DALAM PRAKTIK DI INDONESIA - djunyanto Thriyana (Dialogia Iuridica, 2020)
Abstract Banking is categorized as one of the very risky industries. The collapse of the banking industry can cause an economic crisis in a country. To maintain the health of the industry, it is necessary for all parties involved to run banks based on principle known as prudential banking principle in their daily operation. There are several factors that can reduce the soundness of the bank. One of them is the condition of loan portfolio maintained by the bank which is reflected by Non Performing Loan or NPL ratio. The higher the NPL ratio, the worse the loan portfolio of the bank. This could affect to the bank liquidity, Rentability, solvability and finally the overall bank’s ability to survive. To maintain a low NPL ratio, banks must handle NPL in an effective and efficient manner. This paper tries to describe the way banks in Indonesia deal with NPL in practice and concludes that most banks apply the restructuring and litigation methods.